مساهمة في الدراسة التصنيفية للدوارات Rotifera في بعض أحواض تربية الأسماك في مزرعة شطحة (الغاب) - مسعود مسلم (Latakia University Journal -Biological Sciences Series, 2018)
تعتبر الدوارات Rotifera من العوالق الحيوانية الهامة في النظام البيئي لبحيرات المياه العذبة، وتشكل مع رتبة متفرعات القرون Cladocera و صف مجذافيات الأرجل Copepoda معظم عوالق المياه العذبة التي تحتل بدورها المستوى الغذائي الثاني والثالث في السلاسل الغذائية للأسماك. أجريت لأول مرة دراسة تصنيفية وبيئية لشعبة الدوارات في خمسة مواقع ضمن أحواض تربية الأسماك في منطقة الغاب بمحافظة حماه التي تعد مساهمة في تحديد التنوع الحيوي المائي السوري. تمت الدراسة على 100 عينة كانت قد أخذت من هذه المواقع في الفترة الزمنية الواقعة ما بين آذار من عام 2004 وشباط من عام 2005. وقد تم تسجيل وجود عشرين نوعاً تابعاً إلى أحد عشر جنسا ًمنتمياً بدوره إلى ثماني فصائل. أكثرها مصادفة كانت أفراد فصيلة Brachionidae وضمت ثمانية أنواع، وأقلها أفراد فصيلة Trichocercidae وضمت نوعاً واحداً فقط وتعتبر الأنواع P.dolichoptera ، B. angularis ، K.quadrata, F. Longiseta ذات انتشار واسع وأهمية كبيرة في مجال تربية يرقات الأسماك في مراحلها الأولى في أحواض حضن اليرقات في المزارع السمكية لمنطقة الدراسة . درست بعض الخصائص الفيزيائية والكيميائية للمياه في مواقع الدراسة وتبين أن الاستخدام الكبير للمركبات العضوية في الحقول الزراعية ومخلفات الحيوانات الداجنة الموجودة حول أحواض التربية السمكية أدى إلى ارتفاع نسبة المواد العضوية بينما درجة الحرارة ودرجة الـ PH كانتا عاملين محددين في مصادفة الأنواع المسجلة خلال فترة البحث. The Rotifera is considered one of the important zooplankton in the environmental system of the Fresh water lakes. So together with the order of Cladocera, and the class of Copepoda, it will form most of the fresh water plankton which in turn occupies the second and third levels through the nutrient series of the fish . Classification and environment of study of Rotifera phylum in five positions within fish breeding basins in Al-Ghab region in Hama province is done for that first time and considered a contribution to determine the Syrian water Biodiversity. The study is done on 100 samples which have been taken from those locations in the period between March 2004 and February 2005. About twenty species belonged to eleven genera which by turn are related to eight families registered. The most encountered is brachionidae individuals family which includes eight species, and the least encountered is trichocercidae individuals family which includes just one species. So these Following species : P. dolichoptera, B. angularis, K. quadrata, F. Longiseta are widespread and of great value in the field of breeding the fish larvae through their first stages in larvae incubation basins in the fishing Farms of the study region . Some physical and chemical characteristics of water in the study positions have been studied. Thus it becomes clear that the great use of organic compounds in the agriculture fields and the domestic animals scraps existed around the fish breeding basins lead to cause an increase of the organic substances ratio while the temperature and PH, where specific factors in encountering the species recored through the research period.